Treatment and prevention of arresive bleeding in patients with pancreonecrosis. - V. V. Boyko; V. N. Lykhman; S. V. Tkach; A. A. Merkulov; I. V. Volchenko (Medičnì Perspektivi)
The article is devoted to the study of acute necrotizing pancreatitis, which leads to the development of various fluid pathologies different in pathogenesis and time, which in turn can lead to an arrosive bleeding. Diagnostic-treatment ispresented algorithm with the active use of modern methods of hemostasis in patients with arrosive bleeding developed against the background of pancreatonecrosis.